PENGARUH PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) BERBANTUAN MEDIA SMART AND INTERESTING CARD (SIC) TERHADAP HASIL BELAJAR SISWA - Pratiwi, Kun Khuriya; Santosa, Nurwachid Budi (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2013)
This experiment aimed to determine the influence of studentâs learning outcomes ofÂ Senior High School (SHS) in Parakan through the application of TAI (Team AssistedÂ Individualization) assisted of SIC (Smart and Interesting Card) media on the subject of redoxÂ reaction. The population in this experiment were X grade students Senior High School (SHS) inÂ Parakan of the school year 2011/2012. Determination of the sample used cluster randomÂ sampling system that obtained two classes where X-3 as an experimental group that was treatedÂ by using TAI method assisted by SIC media and X-4 as a control group that was treatedÂ conventional methods. The research data was obtained by the method of documentation, testing,Â questionnaire and observation. The final analysis methods are normalization test, the similarity ofÂ two varians test, difference of two average test, gain test, biserial correlation, determinationÂ coefficient and analysis of questionnaire and observation sheet. The results showed thatÂ experiment class better than the control class. The results of study obtained results of theÂ experimental group had an average 76,78 and a control group had an average of 67,82. TAIÂ method assisted by SIC media give contribution to the learning outcome as 30%.Key words: TAI learning, SIC mediaÂ